Pengaruh Model Pembelajaran Kontekstual terhadap Kreativitas Menulis Puisi Siswa Kelas 5 Sekolah Dasar - Fatihah, Erina (Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This study explores the impact of Contextual Learning Model (CLM) on the creativity of writing poetry in fifth-grade elementary school students. An experimental method was employed by dividing students into an experimental group receiving CLM and a control group receiving conventional teaching. Data were collected through creativity tests for writing poetry before and after the intervention. The results indicate a significant improvement in poetry writing creativity in the experimental group compared to the control group. Students engaged in contextual learning demonstrated better abilities in producing unique and meaningful poetry. CLM provides opportunities for students to actively participate in the learning process, fostering creative thinking and linking learning to real-world contexts. This research contributes to practical and theoretical understanding of the effectiveness of CLM in enhancing poetry writing creativity at the elementary school level.